Goat farming as a profitable alternative for tribal farmers: An experience from FFP at Chhattisgarh - Mooventhan, P.; Verma, Hem Prakash; Singh, Suman (Indian Farming, 2025)
Goat farming has proven to be a profitable and sustainable livelihood option for small, marginal, and landless farmers in the tribal-dominated regions of Chhattisgarh under the Farmer FIRST Programme. The initiative, implemented by the ICAR-National Institute of Biotic Stress Management (NIBSM), Raipur, was carried out in five villages of Kasdol block, Balodabazar district, where a total of 83 improved breed of goats (Sirohi, Jamunapari, and Barbari) were distributed among farmer groups comprising 15–20 members each. Capacity-building programmes, along with vaccination and healthcare support, were provided in collaboration with the local veterinary department to ensure scientific management and enhance productivity. The economic analysis revealed that the total annual cost of rearing amounted to `1,72,330, while the gross income from the sale of live goats was `5,67,600, resulting in a net income of `3,95,270 and a benefit: cost ratio (B:C) of 3.29. These results clearly demonstrated that goat farming is a highly remunerative enterprise requiring low investment and minimal resources. The initiative not only enhanced income and livelihood security among tribal farmers but also reduced seasonal migration, promoted rural entrepreneurship, and strengthened women’s participation in livestock-based enterprises, thereby contributing significantly to economic resilience and sustainability in rural communities.